The PIPER survey - I. An initial look at the intergalactic globular cluster population in the Perseus cluster - Harris, William E.; Brown, Rachel A.; Durrell, Patrick R.; Romanowsky, Aaron J.; Blakeslee, John; Brodie, Jean; Janssens, Steven; Lisker, Thorsten; Okamoto, Sakurako; Wittmann, Carolin (The astrophysical journal, 2020)
We describe the goals and first results of the Program for Imaging of the PERseus cluster of galaxies (PIPER). The first phase of the program builds on imaging of fields obtained with the Hubble Space Telescope (HST) Advanced Camera for Surveys (ACS)/WFC and WFC3/UVIS cameras. Our PIPER target fields with HST include major early-type galaxies including the active central giant NGC 1275, known ultra-diffuse galaxies, and the intracluster medium. The resulting two-color photometry in F475W and F814W reaches deep enough to resolve and measure the globular cluster (GC) populations in the Perseus member galaxies. Here we present initial results for eight pairs of outer fields that confirm the presence of intergalactic GCs (IGCs) in fields as distant as 740 kpc from the Perseus center (40% of the virial radius of the cluster). Roughly 90% of these IGCs are identifiably blue (metal-poor) but there is a clear trace of a red (metal-rich) component as well, even at these very remote distances.
Gesehen am 23.04.2020